Development of Learning Module Cooperative Learning Type Student Facilitator And Explaining in Construction Cost Estimation Subject - Rahmatullah, Ramadhani; Syahril, Syahril; Abdullah, Rijal (Journal of Education Technology, 2021)
The background of this research is that students' understanding of the material for Estimating Construction Costs is not maximal, marked by the low learning outcomes of students in Construction Cost Estimation subjects, teacher-centered learning orientation, students have not been able to learn independently and only rely on explanations of material from the teacher, and materials. the teaching available has not been able to facilitate students to learn independently and thoroughly. The research objective was to develop and reveal the validity, practicality, and effectiveness of the Student Facilitator and Explaining Cooperative Learning module to increase student activity and learning outcomes through increasing critical thinking skills, creative thinking skills, communication skills, and collaboration skills. This research was conducted using the research and development (Research and Development / R&D) method using the Four-D (4D) development model. The Four-D (4D) development procedure is Define (restriction), Design (design), Develop (development), and Disseminate (deployment). The results obtained from this study were the validity of the module based on the Cooperative Type Student Facilitator and Explaining which was declared valid on the material aspects in the module with a total value of validity was 99.3% and the module format aspect was declared valid with a total value of 91.7. The Student Facilitator Cooperative Learning Module Type is stated to be practically based on the teacher's assessment with a practicality value of 88.62% in the very practical category and 88.98% in the very practical category. The module effectiveness value shows an increase in the pretest score of 55.00 to 84.58 in the post-test score with the gain score in the medium category. %. Based on the findings of this study, it is concluded that the module based on the Cooperative Type Student Facilitator and Explaining is valid, practical, and effective to be used as a learning medium in the Construction Cost Estimation subject.